Differences in management and outcomes between male and female patients with atherothrombotic disease: results from the REACH Registry in Europe - Morrell, Jonathan; Zeymer, Uwe; Baumgartner, Iris; Limbourg, Tobias; Röther, Joachim; Bhatt, Deepak L.; Steg, Ph. Gabriel (European journal of cardiovascular prevention & rehabilitation, 2011)
Although guidelines recommend similar evaluation and treatment for both sexes, differences in approach and outcomes have been reported.Prospective, observational registry.Consecutive patients at high cardiovascular risk were assessed for risk factors and management at baseline, and followed-up for 2 years.Twenty-two thousand and twenty-eight patients with documented arterial disease (symptomatic) or three or more atherothrombotic risk factors (asymptomatic) completed the 2-year follow-up of the REduction of Atherothrombosis for Continued Health Registry in Europe (women, 31.5%; men, 68.4%). Women patients were 3.3 years (mean) older than men. Few differences were observed between asymptomatic men and women in risk factor profile or management at baseline. Higher proportions of symptomatic women than men had diabetes (P < 0.001), hypertension (P < 0.0001), elevated total cholesterol levels (P < 0.0001) or elevated triglycerides (P < 0.01). A much lower proportion of women than men were current smokers (asymptomatic, 14.6 vs. 29.3%; symptomatic, 11.9 vs. 19.5%, both P < 0.0001). Within the symptomatic population, women received antithrombotic agents (91.8 vs. 94.9%, P < 0.0001) and lipid-lowering agents (68.2 vs. 73.1%, P < 0.0001) less frequently than men. After multivariate adjustment, fewer symptomatic women than men had undergone coronary revascularizations at 2 years (odds ratio, 0.72; 95% confidence interval, 0.61-0.85). There were no differences in primary outcomes, including cardiovascular death/myocardial infarction/stroke (odds ratio, 1.01, 95% confidence interval, 0.93-1.11, P = 0.78), between the sexes.Although no differences were found in cardiovascular event rates at 2-year follow-up, secondary prevention could be improved in women, which might further reduce event rates.
Gesehen am 08.09.2022